(untitled) (London Journal of Medical and Health Research, 2024)
In Brazil, women represent 51.5% of the population and play multiple roles, including family care and household chores, which directly impacts their health. IBGE data indicates that women are the main users of health services, accounting for 78% of users. Corroborating their role in modern society, there have been changes in the mortality profile of women, which is the focus of this study. The aim of the study was to analyze the main causes of mortality among women of childbearing age in a municipality in the interior of the state of Rio Grande do Sul, making a comparison with a previous study carried out by the authors. The data shows that 197 deaths were recorded, with a higher prevalence in the 40-49 age group. The main causes of death were neoplasms, circulatory diseases, infectious diseases and external causes. This suggests the need for health promotion, early diagnosis and appropriate treatment of diseases to prevent early mortality, highlighting the importance of public health policies.